1998
DOI: 10.1093/jnci/90.6.447
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Angiogenesis-Related Genes and Progression of Human Ovarian Carcinomas in Nude Mice

Abstract: The expression of various genes that regulate angiogenesis in human ovarian carcinomas is associated with the pattern of the disease and its progression. Therefore, targeting specific genes that regulate angiogenesis could offer new approaches to the treatment of ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
208
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(214 citation statements)
references
References 58 publications
5
208
0
1
Order By: Relevance
“…In addition, it has been reported that there is a direct correlation between high levels of CXCL8 and tumor angiogenesis, progression and metastasis in nude xenograft models of human cancer cells [83,85]. In an experimental model of ovarian cancer, the expression of CXCL8 was directly correlated with neovascularization and poor survival [86]. CXCL8 may also play an important role in angiogenesis in prostate and breast cancer as serum levels of CXCL8 are elevated in patients with prostate and breast cancer, and correlate with disease stage [87][88][89][90][91].…”
Section: Chemokines In Angiogenesismentioning
confidence: 99%
“…In addition, it has been reported that there is a direct correlation between high levels of CXCL8 and tumor angiogenesis, progression and metastasis in nude xenograft models of human cancer cells [83,85]. In an experimental model of ovarian cancer, the expression of CXCL8 was directly correlated with neovascularization and poor survival [86]. CXCL8 may also play an important role in angiogenesis in prostate and breast cancer as serum levels of CXCL8 are elevated in patients with prostate and breast cancer, and correlate with disease stage [87][88][89][90][91].…”
Section: Chemokines In Angiogenesismentioning
confidence: 99%
“…24 We and others have utilized intraperitoneal injection of ovarian cancer cells into nude mice to study metastatic ovarian cancer since this model mimics the pattern of tumor spread in human patients with advanced ovarian carcinoma. 25,26 Female athymic nude mice (NCr-nu) were purchased from the National Cancer Institute, Frederick Cancer Research and Development Center (Frederick, MD) and maintained in specific pathogen-free conditions. The animals were cared for according to guidelines set forth by the American Association for Accreditation of Laboratory Animal Care and the US Public Health Service Policy on Human Care and Use of Laboratory Animals.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…The contribution of CXCL1, 2, and 3 to angiogenesis and tumor progression has been shown in immortalized murine melanocytes (Luan et al, 1997;Owen et al, 1997). Elevation of tumor associated CXCL8/IL8 within tumors correlates with neovascularization and is inversely correlated with survival in patients with ovarian carcinoma and non-small-lung cell carcinoma (Smith et al, 1994;Yoneda et al, 1998), whereas CXCL10 mediates its angiostatic activity via CXCR3 on endothelium (Strieter et al, 2006). Taken together, the up-regulation of angiogenic CXC chemokines (CXCL2, 3 and 8) and down-regulation of angiostatic CXC chemokine (CXCL10) observed in CCA-PBLs may reflect the tumor angiogenic environment in CCA.…”
Section: Discussionmentioning
confidence: 99%